NI Index of Production Methodological Note to explain differences in published series (from Q1 2014) due to moving from X-12 ARIMA to X-13 ARIMA SEATS for Seasonal Adjustment. ([2018]) - Northern Ireland Statistics & Research Agency,
No abstract available